The Outcomes of Accidental Ingestion of Hand Sanitizer - Alizadeh, Anahita; Moazen, Nasrin; Pourbadakhshan, Nafisseh; Mostafazadeh, Babak (International Journal of Medical Toxicology and Forensic Medicine, 2021)
Background: children are exposed to numerous chemicals, such as hand sanitizers and their associated poisoning. Awareness of such poisoning symptoms and their management is critical for healthcare providers, as it can induce dangerous conditions. This study evaluated the clinical and paraclinical parameters of children who ingested hand sanitizers. Methods: In the first 6 months of 2020, the cases of children who accidentally ingested hand sanitizer and were referred to Akbar Hospital in Mashhad City, Iran (Referral pediatric poisoning center) were evaluated in this cross-sectional study. The relevant medical information and laboratory parameters were recorded. Results: In total, 20 patients were evaluated; of whom, 80% were male. The Mean±SD age of the study subjects was 4.9±4.2 years (2-15y). The ingestion was accidental in the study participants. The amount of ingestion approximately equaled a sip (3-7cc). All clinical and laboratory parameters were normal according to their age. Only 1(5%) case presented metabolic acidosis. No study subject manifested hypoglycemia or the loss of consciousness. Thus, they only received supportive care and were observed for ≥12 hours. Conclusion: Based on the present study results and absence of symptoms in the explored cases of hand sanitizer ingestion, the suitability of hand sanitizer solutions. Therefore, the formulation of these products should be carefully evaluated.